Analisis Rancang Bangun Sistem Informasi Menggunakan Metode Least Square untuk Memprediksi Hasil Penjualan Beras - Nugraha, Arif Bakti (Masoem University, 2024)
Mang Jana rice shop (TB MJ) is a CV-shaped company which operates in the field of selling basic necessities which is located in Bandung City, precisely in Ujungberung District. This shop experiences an increase in sales every month. In this case it is necessary to predict the number of sales in the coming period. Forecasting (forecasting) means estimating what will happen in the future, and planning means deciding what to do once it is done. The Least Square method is a sales forecasting method by minimizing the criterion function of the sum of the squares of forecasting errors, so that it can be used for sales forecasting. The Least Square Method is an analysis method that aims to predict the future by looking for similarities in data trends which includes time series analysis for two cases: even and odd data. The amount of data may increase. The results of the study show that the application built is very helpful for the rice shop in making predictions so that it is more precise and accurate.